2012
DOI: 10.3846/20296991.2012.757438
|View full text |Cite
|
Sign up to set email alerts
|

Methodology Devising for Bucket-Wheel Excavator Surveying by Laser Scanning Method to Determine Its Main Geometrical Parameters

Abstract: The application of laser scanning techniques to bucket-wheel excavator surveying seeks primarily to determine the machines' key geometric parameters and to establish realistic mathematical descriptions of their movement dynamics in 3D space. The data will be used to visualize excavator movement and to control the coal extraction process in real time. The measurements take place at Doly Nástup Opencast Coal Mine, Tušimice, North-Bohemian Lignite Coal Field, Czech Republic. GNSS technology and inclinometric meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Subsequently, an algorithm [8] was developed that incorporated the results of the measurements of the individual measuring and gauging instruments and allowed calculations of the spatial position of the wheel centre in any general position of the excavator [10]. Somewhat more complex is the modelling of the shape of the material to be placed on the spoil heap by tracked stackers using the throw parabola [4].…”
Section: Basic Components Of the Systemmentioning
confidence: 99%
“…Subsequently, an algorithm [8] was developed that incorporated the results of the measurements of the individual measuring and gauging instruments and allowed calculations of the spatial position of the wheel centre in any general position of the excavator [10]. Somewhat more complex is the modelling of the shape of the material to be placed on the spoil heap by tracked stackers using the throw parabola [4].…”
Section: Basic Components Of the Systemmentioning
confidence: 99%
“…An average achieved accuracy of inclinometer Sitall-015-180-2 STS-232 is ±0.0046°. There were calculated standard error of the wheel center coordinates of each affected precision surveying and measuring instruments (Table 4) (Vrublová et al 2012). Compared with the previous period, there is a noticeable qualitative shift in determining the accuracy of the wheel centre.…”
Section: Analysis Of Internal and Real Accuracy Of The System For Determination Of Excavator Bucket Wheel Position For The Period 2011-20mentioning
confidence: 99%
“…By adopting a bucket wheel excavator-belt conveyor continuous mining system, the Fortu surface mine and Bergheim surface mine of the Rhine Lignite Company in Germany have achieved production scales of 50 Mt/a and mining ergonomics above 120 t/d. Currently, the world's largest bucket wheel excavator reports a daily production of 24×10 4 m 3 /d (Johnson & King, 2010;Vrublová et al, 2012;Daniel & Orban, 2010). By our research experiences of the bucket wheel excavator system for many years, it is found that the current adjustment speed rule for the rotary speed of the bucket wheel excavator body is unreasonable.…”
Section: Introductionmentioning
confidence: 95%